Comparing numerical methods for the solution of Cauchy reaction-diffusion problems - Chowdhury, Md. Sazzad Hossien; Hashim, Ishak; Ismail, Ahmad Faris (2009)
In this paper, the solution of Cauchy reaction-diffussion problems is presented by homotopy-perturbation method (HPM). Reaction-difussion equations have special importance in engineering and sciences and constitute a good model for many systems in various fields. The HPM yields an analytical solution in terms of a rapidly convergent infinite power series with easily computable terms. Comparison between the solutions of HPM and the Adomian decomposition solutions, variational iteration solutions, homotopy analysis solutions and the exact solutions are made. The results reveals that the HPM is a powerful and efficient tool for PDEs.